A Comparative Study of Topical Ketamine and Diclofenac Sodium as Oral Rinse in The Management of Post Tonsillectomy Pain - Narasareddy, Lasya Raj; Seekala, Siddartha; Nagisetty, Sindhuja; Koduru, Jagruthi (Journal of Neonatal Surgery, 2025)
Introduction: Tonsillectomy is one of the commonest procedures performed by an otorhinolaryngologist, representing approximately 20-40% of the surgeries performed.1 Tonsillectomy is associated with unacceptable pain during the first 24 hours after surgery.2 Pain management in the immediate postoperative period following tonsillectomy is very essential to ensure proper oral intake. There are various methods of administering analgesics- oral, per-rectal, intravenous, intramuscular, topical. Topical approaches have the advantage of pain control with good patient acceptability in the immediate postoperative period.3 Topical approach helps in delivering the drug at the site of action and hence has better pain relief, with less systemic side effects due to less systemic absorption. Ketamine and Diclofenac Sodium are non-opioid analgesics which can be used in reducing post tonsillectomy pain in adults. Ketamine, a potent N-Methyl-D-Aspartate (NMDA) receptor channel blocker, acts on central nervous system as well as peripheral receptors. It has an analgesic, anti-inflammatory property and inhibits wind up pain and hyperalgesia. It has anti-hyperalgesic effects in subanaesthetic doses. Diclofenac, a non-steroidal anti-inflammatory drug (NSAID) has analgesic properties. It is a Cyclooxygenase (COX) inhibitor and reduces the production of prostaglandins which are the chemical mediators of pain. There are various methods of analysing pain- Visual Analogue scale (VAS), objective pain scale, faces pain scale, behavioural rating scale, numerical rating scale (NRS). Visual Analogue Scale (VAS) is a validated pain measuring scale for adults. Aims: To compare the effectiveness of Ketamine and Diclofenac Sodium given as oral rinse in reducing post tonsillectomy pain in adults. Material And Methods: Data was collected from a sample of 60 patients aged 18-30 years who have undergone tonsillectomy in a tertiary care centre from April 2024 to March 2025. Informed consent was taken from the patients and their bystanders. 30 cases for each group were selected by using simple random sampling method. Tonsillectomy was performed by dissection and snare method. Patients in group 1 received Ketamine solution 20 mg dissolved in 10 ml saline. Patients in group 2 received Diclofenac Sodium tablet (dispersible) 50 mg in 10 ml saline. The drugs were administered as an oral rinse -2 times on the day of surgery and at an interval of 8 hours on the first postoperative day. Baseline VAS score was assessed. Pain was assessed half an hour after giving each oral rinse. The onset and duration of analgesia, the time of first oral feed, the need for first rescue analgesic, and side effects of the drugs were noted. Results: Topical Ketamine has longer duration of analgesia compared to topical Diclofenac Sodium. The patients in Ketamine group had lesser need for rescue analgesics and were able to have their first oral feed earlier when compared to those in Diclofenac group. There were no adverse effects in either groups. Conclusion: Topical Ketamine and topical Diclofenac Sodium can be used to reduce post tonsillectomy pain without any adverse effects; topical Ketamine being comparatively better.